Old cowboys never die - Johnstone, William W.; Johnstone, J. A. (Pinnacle Books/Kensington Publishing Corp., 2023)
They say you can't teach an old dog new tricks. But old cowboys? that's a different story--especially when those cowboys are trail-hardened cattlemen like Casey Tubbs and Levi Doolin. When these longtime buddies learn that their bosses are getting out of the beef business, there's nothing left to do now but deliver the last two-thousand cows to Abilene and collect their pay. Except for one problem. Their bosses' lawyer is skipping town with all the workers' cash, which means Tubbs and Doolin have on last job to do--steal it back. Sure, pulling off a robbery is a new challenge for these old boys. But they've learned a lot of tricks over the years, and onces they pull off the perfect crime--and get away with it--Tubbs and Doolin start thinking they may have missed their calling in life. this could be the start of a whole new career--as outlaws. So begins the wild, wild story of tow old cowboys who are one step ahead of the law--and the young U.S. marshal who's determined to catch them.